The effect of nutritional risk management program on the growth and development of infants and toddlers with congenital heart disease after discharge - Ya-Li Huang; Ya-Li Huang; Wen-Yi Luo; Wen-Yi Luo; Wen-Yi Luo; Xie-Lei Wang; Xie-Lei Wang; Feng Zheng; Feng Zheng; Jian-Hua Gao; Jian-Hua Gao; Ming-Xia Chen; et al. (Frontiers Media S.A., 2024)
ObjectiveTo evaluate the effect of nutritional risk management program on the growth and development of infants and toddlers with congenital heart disease (CHD) after discharge.MethodsInfants and toddlers with CHD discharged from a children's specialized hospital in southeast China were selected as the research subjects. The subjects were divided into the intervention group and the control group. The intervention group underwent a nutritional risk management program combined with traditional follow-up after discharge, whereas the control group received traditional follow-up after discharge. The primary outcome measure were the height-for-age Z-score (HAZ), weight-for-age Z-score (WAZ), and weight-for-height Z-score (WHZ) at different time point and the percentage of growth and development curves were also recorded and analyzed.ResultsThere were no statistically significant differences in general characteristics between the two groups. However, in the intervention group, the percentages of HAZ < −2, WAZ < −2, and WHZ < −2 were lower than those in the control group at 3rd and 6th months after discharge (P < 0.05). The percentage of growth and development curves (3%-97%) was higher than that in the control group (P < 0.05). The readmission rate within 6 months after discharge in the intervention group was lower than that in the control group (P < 0.05).ConclusionImplementing nutritional risk management program for infants and toddlers with CHD after discharge can help improve postoperative malnutrition, promote growth and development and achieve catch-up growth as soon as possible.